The Impact of the Non-life Insurance Penetration on the Economic Growth of Developing Countries: Panel Data Analysis - Sihem, Ezdini (International Journal of Economics, 2025)
Purpose: This study explores the impact of non-life insurance industry performance on economic growth in 10 developing countries (Australia, Austria, Canada, Denmark, Finland, France, Italy, Luxembourg, Norway, and Portugal). Methodology: Insurance penetration is measured through proxy such as non-life insurance with the time-series statistics covering the period from 1990 to 2021. The ordinary least square regression was adopted for the testing of the hypotheses. The results are based on panel data models and panel cointegration. Findings: The outcomes of the study showed that non-life insurance penetration had a substantially positive effect on the economic growth in 10 developing countries during the period from 1990 to 2021. The results based on panel data models and panel cointegration suggests that Non-life insurance has a positive and significant effect on the economic growth of the chosen countries. Also, it shows that the application of the rule of law had a positive effect on the developing economies. On the other hand, the higher the level of education, the more people are aware of the application of non-life insurance, which positively affects economic growth. Furthermore, culture and population density have a positive impact on economic growth. Unique Contribution to Theory, Practice and Policy: The study recommends an improved modification in insurance products, especially in non-life businesses to availing clients the chance of choosing from a diversity of products. The study, therefore, recommends an increase in the awareness of non-life insurance services for its impact to be felt at all levels and to encourage participation.